Achieving universal health coverage through community empowerment: a proposition for Bangladesh - Joarder, Taufique; Sarker, Malabika (© 2014 Medknow Publications, 2016)
This note was published in Indian Journal of Community Medicine [© 2014 Medknow Publications] and the definite version is available at: http://www.ijcm.org.in/article.asp?issn=0970-0218;year=2014;volume=39;issue=3;spage=129;epage=131;aulast=Joarder